The Effect of Regional Original Revenue on Regional Financial Performance: Test the Role of Economic Growth as Moderation (Study on Regency / City in Bali Province) - Antari, Sang Ayu Made Dwi; Darmayanti, Ni Putu Ayu (CV. Lenggogeni Data Publishing, 2025)
Regional financial performance describes the measure of the success of local governments in managing regional finances effectively and efficiently to meet regional needs and improve public services. This study aims to determine the effect of local revenue on local financial performance with economic growth as a moderator. The type of data used in this study is secondary data obtained through the official website Badan Pusat Statistik (BPS) and Direktorat Jenderal Perimbangan Keuangan (DJPK). The population in this study were all regencies / cities in Bali Province for the 2018-2023 period, in total 9 regencies / cities. The method of determining the sample in this study is the sensus method with saturated sampling technique, using the entire population as a research sample so that the sample used in this study for 6 years with a total of 54 samples. The analysis technique used is descriptive analysis and inferential analysis (Moderate Regression Analysis). Based on the test results, it was found that local revenue has a positive and significant effect on regional financial performance, and economic growth can moderate the effect of local revenue on regional financial performance